Native Aortic and Tricuspid Valve Endocarditis Complicated by Embolic ST Elevation Myocardial Infarction - Mumtaz Zaman; Richard Loynd; Anthony Donato (Case Reports in Cardiology)
Acute myocardial infarction due to a coronary embolic event can occur as a complication of infective endocarditis in up to 2.9% of cases and can frequently be the presenting symptom. A 35-year-old female presented with 4 hours of typical chest pain and was found to have ST elevations in inferior leads as well as an elevated serum Troponin I of 8.29 ng/ml (normal: <0.06 ng/ml). Urgent cardiac catheterization revealed total occlusion of the right coronary artery without other coronary disease or collaterals. Following a failed attempt at thrombus extraction, a 3.0×38 mm bioabsorbable drug-eluting stent was placed. Echocardiography then revealed large mobile aortic valve vegetations with the largest measuring 1.4×1.7 cm, severe tricuspid regurgitation with a 1.1×0.5 cm mobile vegetation on the anterior leaflet along with a patent foramen ovale with right-to-left shunting. Blood cultures identified Enterococcus faecalis in 4 of 4 vials. The patient underwent urgent replacement of tricuspid and aortic valves as well as 6 weeks of IV antibiotics followed by chronic antibiotic suppression.